The Application Value of Personalized 3D Printing Navigation Molds in Neurosurgery - Hou, Lijie; Zhang, Jian; Meng, Ke; Xue, Yunpeng; Feng, Xin (Journal of Neurological Surgery Part A: Central European Neurosurgery)
Abstract Background: Most neurosurgical procedures have the problems of high cost, large technical differences and high incidence of complication rate.Based on the clinical advantages of 3D technology in surgical procedures, it is necessary to develop an application method for personalized navigation molds that use 3D printing technology in precise and minimally invasive directions,analyze the clinical application of this technology in intracerebral hemorrhage, hydrocephalus, and brain abscess, and expand the research on the clinical application value range of this technology in neurosurgery. Methods: According to the patient specific brain CT imaging data, reconstructed the three-dimensional structure of intracranial lesions or target structures, constructed a three-dimensional model of important brain regions, allowed doctors to accurately locate the location of intracranial lesions under conditions equivalent to direct vision, analyzed the morphology and size of lesions, and performed precise puncture positioning. Based on patient specific differences, designed the best path 3D printing navigation molds to improve the puncture accuracy of targeted intracranial lesions and truly achieved personalized medical treatment. Results:This article focuses on 5 cases of intracerebral hematoma, 2 cases of hydrocephalus, and 2 cases of brain abscess in the neurosurgery department of the Third Bethune Hospital of JiLin University from September 2020 to January 2022. Neurosurgical puncture and drainage was performed with 3D printing navigation molds, the basic situation of the surgery was analyzed ,the lesion clearance rate was over 70% and the average puncture error was 2.86mm.All the 9 patients recovered well after surgery, and no infection or death occurred. Conclusion: The personalized 3D printing navigation molds provided in this study is beneficial for clinical doctors to accurately locate intracranial lesions or target three-dimensional structures during surgery. It has the advantages of cheap equipment, simple operation, and accurate positioning, and is suitable for promotion in grassroots hospitals.